COMPANY LEADERSHIP NARCISSISM ON INTERNAL CONTROL (JURNAL ECONOMICA : Research of Economic And Economic Education, 2023)
This study aims to examine the effect of company leadership narcissism on the company's internal control. The sampling technique used was purposive sampling. Data were obtained as many as 429 samples from the annual financial statements of companies listed on the Indonesia Stock Exchange (IDX) from 2017-2021. Panel data regression with random effects model was used to analyze the research data. The results of this study indicate that there is no significant effect of company leadership narcissism on internal control.